IMPACT OF THE COVID-19 PANDEMIC ON NURSING STUDENTS’ EDUCATION - Bernardes, Viviana; Oliveira Reis, Carla; Ferreira, Luisa; Franco, Filipe (Health and Society, 2023)
Context: With the COVID-19 pandemic, there was an abrupt change in teaching. It is important to analyze the distance education methods used, as there is a need for students to develop skills in direct contact with the client/community. Objectives: to examine and map the scientific evidence on the changes in the teaching of nursing students with the emergence of the pandemic. Methodology: Scoping Review inspired by the principles advocated by the Joanna Briggs Institute, allowed the analysis of articles, establishing the guiding question: “What is the impact of the COVID-19 pandemic on the education process of nursing students?”. Searches were carried out in 3 international databases, in a total of 40 studies, and 17 studies were selected for abstract reading and 1 article from Gray Literature was included, leaving a final sample of 9 studies. Results: The 9 studies analyzed show that the attitude of students towards the abrupt change to distance education is negative and forced teachers to use different teaching strategies, using technology. Conclusion: In the future, it will be possible to develop different education models, as well as specific methods using telenursing and the development of an integrated virtual reality simulation program, or even the development of a hybrid model.